2021
DOI: 10.1016/j.cjco.2021.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants vs Vitamin K Antagonists in Left Ventricular Thrombi: A Systematic Review and Meta-analysis

Abstract: Left ventricular (LV) thrombus formation complicates 15% of acute myocardial infarctions (MIs), and it is even more common in conditions of impaired LV systolic function. [1][2][3] If left untreated, up to 20% of patients can have significant complications, including stroke and systemic embolism. 3 Current consensus guidelines recommend the use of vitamin K antagonists (VKAs) to treat LV thrombi following acute MIs for 3-6 months. 4,5 Direct oral anticoagulants (DOACs) are a preferred alternative to VKAs, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 46 publications
3
25
0
4
Order By: Relevance
“…In the present study, the pooled results showed a similar SSE risk of DOACs with VKAs in patients with LVT. This was in line with the findings of prior studies [8,25,26,30,37,38]. Michael F, et al [37] performed a meta-analysis to compare the safety and efficacy of DOACs versus VKAs for LVT and found a comparable effect in SSE between the two treatments (odds ratio (OR) = 0.83, 95% CI: 0.53, 1.33; p = 0.45).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, the pooled results showed a similar SSE risk of DOACs with VKAs in patients with LVT. This was in line with the findings of prior studies [8,25,26,30,37,38]. Michael F, et al [37] performed a meta-analysis to compare the safety and efficacy of DOACs versus VKAs for LVT and found a comparable effect in SSE between the two treatments (odds ratio (OR) = 0.83, 95% CI: 0.53, 1.33; p = 0.45).…”
Section: Discussionsupporting
confidence: 87%
“…This was in line with the findings of prior studies [8,25,26,30,37,38]. Michael F, et al [37] performed a meta-analysis to compare the safety and efficacy of DOACs versus VKAs for LVT and found a comparable effect in SSE between the two treatments (odds ratio (OR) = 0.83, 95% CI: 0.53, 1.33; p = 0.45). Similarly, in another metaanalysis of Saleh Y, et al [38], the authors observed no sig-nificant difference between rivaroxaban and VKAs in terms of SSE (OR = 0.73, 95% CI: 0.24, 2.22; p = 0.58).…”
Section: Discussionsupporting
confidence: 87%
“…The sub‐optimal TTR may affect the resolution rate of LVT on VKAs, as mentioned in studies conducted by Alcalai et al ., Ratnayake et al ., Zhang et al 16,28,34 . One previous study recommended performing LVT imaging using delayed enhancement CMRI and transesophageal echocardiography, with follow‐up time points in the range of 3–12 months 36 . The diagnostic methods and follow‐up duration of the included studies were not entirely consistent, which may have influenced our findings.…”
Section: Discussionmentioning
confidence: 84%
“…Almost 50% of the studies included in the study by Michael et al . involved abstracts without complete experimental data, 36 which may influence the generalizability of their results. Moreover, more studies comparing DOACs and VKAs in the treatment of LVT have been published recently 15,22,24,26,27,30–34 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several meta-analysis articles have been published comparing VKAs and DOACs in treatment of LVT [17][18][19][20][21][22][23][24]. However, these meta-analyses included only direct comparative studies between VKAs and DOACs, and did not include single-arm studies.…”
Section: Introductionmentioning
confidence: 99%